2022
DOI: 10.1007/s40265-022-01793-1
|View full text |Cite
|
Sign up to set email alerts
|

Teclistamab: First Approval

Abstract: Teclistamab (TECVAYLI ® ), a bispecific antibody that targets CD3 and B cell maturation antigen (BCMA), is being developed by Janssen Research and Development for the treatment of relapsed or refractory multiple myeloma. Teclistamab was recently granted conditional approval in the EU for the treatment of adult patients with relapsed and refractory multiple myeloma who have received three or more prior therapies (including an immunomodulatory agent, a proteasome inhibitor and an anti-CD38 antibody) and have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…Furthermore, several studies showed that the R/R MM patients who had experienced relapse after anti-BCMA CAR-T cell therapy could also benefit from carfilzomib-based therapy, venetoclax-based therapy, and selinexor-based therapy (132)(133)(134)136). In addition, T cell redirecting bispecific antibodies, such as Cevostamab and Talquetamab, have also proved to be feasible salvage treatment after anti-BCMA CAR-T cell therapy and able to induce durable responses (137)(138)(139). Moreover, a phospholipid-drug complex Iopofosine I-131 could also achieve clinical responses in R/R MM patients who had failed in prior anti-BCMA therapy (140).…”
Section: Subsequent Anti-myeloma Therapy After Car-t Therapymentioning
confidence: 99%
“…Furthermore, several studies showed that the R/R MM patients who had experienced relapse after anti-BCMA CAR-T cell therapy could also benefit from carfilzomib-based therapy, venetoclax-based therapy, and selinexor-based therapy (132)(133)(134)136). In addition, T cell redirecting bispecific antibodies, such as Cevostamab and Talquetamab, have also proved to be feasible salvage treatment after anti-BCMA CAR-T cell therapy and able to induce durable responses (137)(138)(139). Moreover, a phospholipid-drug complex Iopofosine I-131 could also achieve clinical responses in R/R MM patients who had failed in prior anti-BCMA therapy (140).…”
Section: Subsequent Anti-myeloma Therapy After Car-t Therapymentioning
confidence: 99%
“…Teclistamab-cqyv is the first T-cell-redirecting bispecific IgG4 antibody against both CD3 and B-cell maturation antigen (BCMA) (Moreau et al 2022 ). Teclistamab has been approved for relapsed or refractory multiple myeloma in patients who have used more than four previous treatment lines (Kang 2022b ). It received a breakthrough designation following a priority review and an accelerated approval.…”
Section: Oncologymentioning
confidence: 99%
“…MsAbs can provide synergistic effects that are capable of overcoming therapeutic barriers and thus address unmet medical needs . In 2022, over 80 msAbs were subjected to clinical trials, , and 9 msAbs were approved by the authorities: catumaxomab (Removab, Trion), blinatumomab (BLINCYTO, Amgen Inc.), , emicizumab (Hemlibra, Genentech), , amivantamab (Rybrevant, Janssen Biotech), mosunetuzumab (Lunsumio, Roche), tebentafusp (Kimmtrak, Immunocore), , faricimab (Vabysmo, Roche, Genentech), , teclistamab (Tecvayli, Johnson&Johnson), , and ozoralizumab (Nanozora, Taisho Pharmaceutical) . These 80 clinical candidates are engineered msAbs covering a broad spectrum of different antibody formats, and new formats are emerging frequently. As of today, there are over 60 different multispecific antibody formats published. , With the growing therapeutic potential, however, the molecular complexity increases, thus intensifying the demand for innovative protein engineering and analytical strategies .…”
Section: Introductionmentioning
confidence: 99%